Efficiently Controlled Callosobruchus maculatus (F.) (Fam. Bruchidae) by Ultraviolet Ray or Microwave Energy in Conjugation with Pirimiphos-Methyl - Negm, Eslam A.; Khalil, Fatma M.; Alkot, Walaa M.; Abouelatta, Ahmed M.; Elmadawy, Alzahraa A. (Fine Chemical Engineering, 2024)
This study aimed to explore novel approaches for effectively managing Callosobruchus maculatus while ensuring minimal impact on human health and the environment. The investigation involved exposing the insects to ultraviolet rays (254 nm) for 24 hours, which did not directly cause mortality in adult C. maculatus but led to a significant reduction in their progeny by 10%. The reduction in progeny further increased when insects were pre-exposed to a sublethal dose of actellic at LC25, resulting in a reduction of 39%. Additionally, ultraviolet rays exhibited a significant ovicidal effect, with hatchability reduced to 26% compared to 73% in the control group. Microwave exposure at a low energy level for 4-6 minutes demonstrated a significant acute lethal effect, reduced progeny, and ovicidal action. Combining microwaves with actellic at LC25 slightly enhanced the lethal effect. In conclusion, this study unveils promising strategies for the effective management of Callosobruchus maculatus, highlighting the potential of ultraviolet rays and microwave energy, either alone or in combination with actellic, while emphasizing the importance of minimizing adverse impacts on both human health and the environment.